THEORETICAL OVERVIEW OF THE DEFINITION “TERM” AND “TERMINOLOGY” IN LINGUISTIC SURVEYS - Akhmedov, Oybek (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article is dedicated to identifying the meaning of the concepts of "term" and "terminology" used in linguistic research and clarifying their scientific-theoretical ideas and overviews put forward by linguists. As well as, in addition to the concepts of "term", "terminology", "atama (in Uzbek)", "istiloh", "nomenclature" and "professionalism". The author expressed his new theoretical views and opinions against to previous theories.